(untitled) (Journal of the Bangladesh Agricultural University, 2010)
A rapid, efficient and reproducible genetic transformation protocol was optimized for four aromatic rice varieties by using the established plant regeneration protocol. Mature embryos were inoculated with Agrobacterium tumefaciens strain EHA105 carrying a binary vector pIG121-Hm with GUS (reporter gene) and hpt (hygromycin resistance) gene and the transformation experiment was performed by optimizing two important parameters viz. infection times and co-cultivation periods. The highest response to GUS assay was showed by Kalizira (70% GUS positive) followed by Pusa Basmati 1 (66.67%) when the explants were inoculated for 25 minutes and co-cultivated for three days. Twenty five minutes infection time (9.44%) and three day co- cultivation period (8.06%) were found effective for percentage of transgenic shoot regeneration. The highest percentage of putative transgenic shoots was regenerated by variety Kalizira (33.33%) followed by Pusa Basmati 1 (20.0%) and Radhunipagol (13.33%). Among the varieties, Kalizira produced the highest percentage (60%) of rooted shoots. Kalizira also showed the highest survival rate in growth chamber (75%) and in field condition (60%). The performance of Tulsimala was poor for almost all the cases. Keywords: Agrobacterium; GUS; hpt gene; Transformation and Aromatic rice DOI: 10.3329/jbau.v7i2.4724 J. Bangladesh Agril. Univ. 7(2): 235-240, 2009